A Study Within (Oz, 1993)
This article is a project of the Italian Studies Program for fourth year students. Text by Ann Shadle, photographs by Ron Kirkam. Twenty-four students, 2 American faculty (from K-State), and 1 Italian faculty from Castiglion Fiorentino participated: Joseph Bentley, David Boone, Craig Dorroh, Thomas Farmer, Stacey Fithian, Tim Hossler, Wayne Johnson, Kevin Keens, Aaron King, Ron Kirkham, Amy McLelland, Todd Meyer, David Pearlman, David Polich, Rhonda Rentfro, Carl Rogers, Milton Rosa, Ann Shadle, Douglas Stockman, Tina Townsend, Andrew VanBlarcum, Jeffery Weiford, Mindy Wieland, Sean Zaudke. Observers (faculty): Paolo Barruchieri, Mick Charney, Richard Hansen.